2005
DOI: 10.1007/s00383-005-1588-1
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative response in necrotising enterocolitis is insufficient to prevent disease progression

Abstract: Necrotising enterocolitis (NEC) is characterised by severe mucosal loss and therefore gastrointestinal (GI) cell proliferation is essential for survival, epithelial repair and recovery of function. Trefoil peptides play a key role in epithelial restitution and repair, and we previously reported a down-regulation of these peptides in NEC. Oral administration of epidermal growth factor has a protective effect in a rat model of colitis. These observations raised the question of a link between the pathogenesis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
0
16
0
2
Order By: Relevance
“…Vieten et al 16 observed that in NEC there is a deficiency of the proliferative activity, incapacitating the neutralization of the rapid epithelium destruction, also associated with the intestinal immaturity of the preterm infants. Corroborating these findings, it was observed a deficiency of the proliferative activity in the intestinal mucosa of the H/R group.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vieten et al 16 observed that in NEC there is a deficiency of the proliferative activity, incapacitating the neutralization of the rapid epithelium destruction, also associated with the intestinal immaturity of the preterm infants. Corroborating these findings, it was observed a deficiency of the proliferative activity in the intestinal mucosa of the H/R group.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The inability of mucosal regeneration in preterm infants may be related to the deficiency of the expression of the peptide trefoil factor, present in mucus and released together with mucin by goblet cells, contributing to the etiopathogenesis of NEC. Trefoil factor plays an important role in the intestinal epithelium, participating in its protection, its restitution and its regeneration 16 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intestinal trefoil factor is developmentally regulated and deficient in the premature neonate [20] . Recent studies demonstrated a lack of trefoil factor expression in response to NEC in the premature gut [53] and an insufficient proliferative response to reverse the mucosal insult observed in NEC [54] . Thus, impaired restitution of the mucosa may contribute to the cascade of bowel necrosis and generalized sepsis characteristic of NEC.…”
Section: Immature Intestinal Motility Digestion and Barrier Functionmentioning
confidence: 99%